INTEGRATION PROCESSES ON CIVIL SERVICE REFORM IN THE EURASIAN SPACE - G. A. Borshevskiy (Vestnik MGIMO-Universiteta)
The article studies the process of reforming the institute of civil service in the countries of the Eurasian space (e.g. Russia, Belarus and Kazakhstan). The integration of national systems of public administration and, in particular, the civil service, is an important factor contributing to the implementation of the centripetal tendencies in the post-Soviet space. The research methodology is based on a combination of comparative legal analysis, historical retrospective method, normalization and scaling, structural-functional and system analysis. A comparison of the legal models of public service was made in research. The author puts forward the hypothesis that it is presence the relationship between the quantitative changes (for example, number of employees) of civil service and the dynamics of macroeconomic indicators (e.g. number of employed in the economy). In this regard were observed common trends. On materials of the statistical surveys were considered quantitative changes in national systems of civil service. The study of the socio-demographic characteristics of the public service (gender, age, profession) allowed to formulate conclusions about the general and specific trends in the reform of the civil service of the analyzed countries. A number of values were first calculated by the author. The work is intended to become the basis for a broad international research on the development of civil service, which is the central mechanism for implementation the integration in the post-Soviet space.